As bonitezas e os desafios de uma educação física pautada nos princípios de Paulo Freire: uma experiência autoetnográfica de uma professora nos primeiros anos de docência - Castro, Esterlandia Souza (2024)
This work emerged from the commitment and understanding that the renewal of teaching and pedagogical practices was an urgent action in schools, and that it needed to be guided by critical and problematizing references. It proposes an approximation between Paulo Freire's Principles and school Physical Education, in an attempt to show paths for Physical Education based on a contextualized, problematizing, dialogical and loving teaching practice. This is a study with a qualitative bias, in which, through autoethnography, I seek to narrate, feel and understand the paths that brought me closer to Paulo Freire and shaped the teacher I am today. And also highlight the main challenges and possibilities found in the training and teaching path, which were necessary to develop teaching practices based on some of Paulo Freire's principles in Physical Education classes. To do this, I initially describe my life story, my training and my encounter with Paulo Freire and the transformations he provoked in me and how this affects my pedagogical practice and that of students. I also describe the classes that were successful within the teaching proposal and also the fruits that I have been reaping in following a path that seeks a liberating education during the last four years (2021-2024), in schools in the city of Fortaleza- Ceará. I finish by analyzing and reflecting on myself, on my role as an educator and the fruits that I have been reaping, with the learning groups, in believing in a teaching practice based on Freire's principles and hopeful that there is still a lot of power to be developed on the teaching floor. school.